Pledges counteract the boomerang effect in a sustainable showering intervention for children - Jeeva Somasundaram; Zhiyu Wang (Communications Psychology)
Abstract Water scarcity has become a growing concern due to climate change. As fresh water is going to become increasingly scarce in the future, inculcating water-conserving habits among young children is very important. We conduct a randomized field experiment that focussed on instilling the behaviour of showering within 5 min among primary school children (N = 1121) in Singapore. Alongside an educational show emphasizing the importance of a 5 min shower, we introduced two commitment interventions—private and public (written) pledges—to nudge children to adhere to the 5 min shower time goal. Unexpectedly, the educational show and the 5 min shower time goal had an undesirable boomerang effect: children with a baseline shower time above 5 min reduced their shower time, while those below 5 min increased it, resulting in no net reduction. The private and public pledge-based commitments effectively countered the boomerang effect, reducing overall shower time and increasing adherence to the 5 min target. The commitment interventions achieved this by increasing the participants’ willingness to meet the target and by ensuring greater reductions for those more willing to reduce shower time.